CAR-NK cells: harnessing the power of natural killers for advanced cancer therapy - dos Reis, Filipa D.; Saidani, Yanis; Martín-Rubio, Paula; Sanz-Pamplona, Rebeca; Stojanovic, Ana; Correia, Margareta P. (Frontiers in Immunology, 2025)
Generation of Chimeric Antigen Receptors (CARs) presented a significant advance in the field of immunotherapy, allowing the targeting of cell-surface expressed molecules in an MHC-independent manner. Arming NK cells with CARs merges their innate natural cytotoxicity with the refined precision of targeted antigen recognition. The success of these therapies hinges on selecting the right tumor-specific targets to ensure effective activation and avoid self-reactivity. Optimization of CAR design and targeting is based on NK cell intrinsic properties (CAR modules and sources of NK cells), as well as on NK-tumor cell interactions (multi-antigen, multi-step, multi-switch). Additionally, the dynamics of tumor infiltration and adaptation to the tumor microenvironment play a critical role in CAR-NK cell efficacy. Combining CAR-NK cell therapies with chemotherapy, radiotherapy, checkpoint inhibitors, and emerging approaches like epigenetic modulators and oncolytic viruses, may address some of these challenges. The development of CAR-NK cell strategies for metastatic disease is especially promising, though the complexities of metastasis require refined targeted designs. As immunomics and multi-omics continue to evolve, the potential for designing more effective CAR-NK cell therapies expands. As results from preclinical and clinical trials unfold, a multidisciplinary approach integrating all those aspects will be key to unlock the full potential of CAR-NK cell-based adoptive transfers.